A prática da pesquisa científica no cotidiano dos docentes universitários da UFPI e suas contribuições para o campus e para a região - Ferreira, Racilda Maria Nobrega (2014)
This dissertation is part of the thematic research practice developed by the faculty of the Federal University of Piauí - UFPI, at Minister Reis Velloso Campus, in the city of Parnaíba. Therefore, it was proposed as a general objective to understand how this practice is being developed by teachers at UFPI in Parnaíba / PI. From this perspective, three objectives were established: identify how the campus of UFPI in Parnaíba has experienced research in their academic context; verify what the contributions are of this research to the campus and the location where the University is located; identify the challenges faced by the research PhD Professor at the Campus. The period clipping chosen for the study is 2008-2012, the period of the implementation of the Restructuring and Extension of Federal Universities project (REUNI). We start from the principle of inseparability of theory and practice, the empirical base as well as the technical support also being addressed in many moments of the dissertation, showing the importance of this correlation. This is a case study. Thus, the study has a quantitative and qualitative approach. The research practice sought theoretical support in the socio-historical approach, as it sought to understand its dynamics from the practice developed by the teachers with graduate stricto sensu training. We used a mixed questionnaire for data collection, which favored the positioning of the survey participants, as well as a report that supported all the part corresponding to the survey of the researches conducted by the faculty of the campus in this period. As results, we point out that, despite the development presented by the Campus over the past ten years, this research has indicated that the dichotomy between teaching and research, and between the practice of research and social reality, is still visible.